Anti-inflammatory effects of MerTK by inducing M2 macrophage polarization via PI3K/Akt/GSK-3β pathway in gout - Chen, Fangfang; Li, Yixuan; Zhao, Li; Lin, Cong; Zhou, Yingzi; Ye, Wenjing; Wan, Weiguo; Zou, Hejian; Xue, Yu (International Immunopharmacology, 2024)
Mer tyrosine kinase (MerTK) has been found to regulate the secretion of inflammatory factors and exert immunosuppressive effects, but its role in gout remains unclear. In this study, we aimed to clarify the immnue effects of MerTK in gout. MerTK in synovium or serum of gout patients was determined by immunohistochemistry, enzyme-linked immunosorbent assay (ELISA), and real-time quantitative polymerase chain reaction (RT-qPCR). In monosodium urate (MSU)-induced gout mice, the effect of MerTK inhibitor (UNC2250) on inflammation and polarization was also assessed. After inhibition, knockdown or overexpression of MerTK, inflammatory response and polarization level in THP1-derived macrophages were evaluated by RT-qPCR and flow cytometry. Regulation of MerTK inhibitors on mitochondrial function and downstream pathway in THP1-derived macrophages were detected. MerTK in synovium and serum of gout patients were increased. MerTK inhibitor stimulated the inflammation and M1 polarization in MSU-induced gout mice. MerTK inhibition, knock-down, or overexpression affected inflammatory response, polarization and mitochondrial function in vitro in gout model. The PI3K/Akt/GSK-3β pathway was identified to reduce after MerTK inhibition and the relevant results were as expected, validated by knock-down or overexpressing MerTK. In conclusion, MerTK was detected to increase in both gout patients and model. MerTK influenced inflammatory response and polarization markers through PI3K/Akt/GSK-3β pathway. Interfering MerTK/PI3K/Akt/GSK-3β axis may provide a new therapeutic target for gout.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Gout; Inflammation response; MerTK; PI3K/Akt/GSK-3β pathway; Polarization